2021
DOI: 10.1158/1055-9965.epi-21-0661
|View full text |Cite
|
Sign up to set email alerts
|

TP53 Pathway Function, Estrogen Receptor Status, and Breast Cancer Risk Factors in the Carolina Breast Cancer Study

Abstract: Background: TP53 and estrogen receptor (ER) both play essential roles in breast cancer development and progression, with recent research revealing cross-talk between TP53 and ER signaling pathways. Although many studies have demonstrated heterogeneity of risk factor associations across ER subtypes, associations by TP53 status have been inconsistent. Methods: This case–case analysis included incident breast cancer cases (47% B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…ence through the ER signaling pathway, which may serve as a prognostic marker [90], ERα activity could repress p53 transcription and potentially lead to decreased apopto and increased tumor cell proliferation [91,92]. This further supports the results, as t TP53 gene was found to be downregulated in EM, OC, CC, and EC.…”
Section: Hormonal Imbalance and Inflammationsupporting
confidence: 79%
See 1 more Smart Citation
“…ence through the ER signaling pathway, which may serve as a prognostic marker [90], ERα activity could repress p53 transcription and potentially lead to decreased apopto and increased tumor cell proliferation [91,92]. This further supports the results, as t TP53 gene was found to be downregulated in EM, OC, CC, and EC.…”
Section: Hormonal Imbalance and Inflammationsupporting
confidence: 79%
“…On the other hand, TP53 hotspot mutations may lead to mutated p53 function and were found to be common among high-grade serous ovarian carcinoma undergoing primary treatment [ 89 ]. The TP53 gene was also shown to have a strong hormonal influence through the ER signaling pathway, which may serve as a prognostic marker [ 90 ], as ERα activity could repress p53 transcription and potentially lead to decreased apoptosis and increased tumor cell proliferation [ 91 , 92 ]. This further supports the results, as the TP53 gene was found to be downregulated in EM, OC, CC, and EC.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies have shown associations of individual risk factors with other molecular markers, such as histologic grade, KI67, and TP53 mutation status within luminal breast cancers. [51][52][53][54] Accordingly, a change in approach may be warranted to better characterize etiologic subtypes of breast cancer with epidemiologic and public health relevance.…”
Section: Conclusion and Recommendations For Future Workmentioning
confidence: 99%
“…RNA-based expression of DNA repair genes is a convenient approach for tracking DNA repair pathway activity. Other RNA-based classifiers, such as those for TP53 mutant-like status ( 20, 21 ), exemplify that RNA-level data can indicate DNA alterations and complement somatic mutation data. For instance, RNA-based TP53 classifiers accurately identify TP53 DNA mutations and predict survival with hazard ratios that are similar to those from DNA-based assays ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other RNA-based classifiers, such as those for TP53 mutant-like status ( 20, 21 ), exemplify that RNA-level data can indicate DNA alterations and complement somatic mutation data. For instance, RNA-based TP53 classifiers accurately identify TP53 DNA mutations and predict survival with hazard ratios that are similar to those from DNA-based assays ( 20 ). We hypothesized that relative expression levels of core mediators of error-free and error-prone genome maintenance pathways could be used to build RNA expression-based classifiers for DNA repair pathways.…”
Section: Introductionmentioning
confidence: 99%